Use of vapochromic crystals to measure the concentration of a gaseous throughflow at the solid-fluid interface. (December 2018) - Sangan, C.M.; Pountney, O.J.; Scobie, J.A.; Cochrane, B.; Stubbs, C.; Raithby, P.R.
Highlights: Vapochromic crystals reversibly change colour with adsorption and desorption of water. Their suitability for measuring gas concentration at a solid-fluid interface has been studied. The colour-change of the crystals was shown to exhibit a pronounced hysteresis. Temperature and viewing and illumination angles also affects colour-change. The applicability of the crystals for experimental fluid dynamics research is demonstrated. Abstract: This paper demonstrates the potential of vapochromic crystals as a sensing medium for measurements of local species concentration. Vapochromic crystals exhibit a reversible colour change based on the adsorption and desorption of water. As the water content of the crystals changes so too does the wavelength of light that they reflect ( i.e. they change colour). In the situation where humid air mixes with a dry gas, the resulting specific humidity of the mixture can be related to the concentration level of the dry gas through a simple mass balance. As far as the authors are aware, this is the first time that vapochromic crystals have been used in this context. A number of the factors that affect the colour change of the crystal are investigated through simple flat plate experiments in a small wind tunnel. In all experiments, the hue and intensity of the vapochromic crystal was measured as a function of local dry gas concentration; in this case CO2 . Green intensity levels exhibited the broadest activity over the widest range of CO2 levels, and was therefore used to quantify concentration. The crystals demonstrated a pronounced hysteresis, where the adsorption and desorption of water into the crystal structure was shown to occur at different concentration levels. The transition band was also shown to be highly temperature dependent when tested over a range of 22–44 °C. The vapochromic crystals were assessed for repeatability and found to sense the local CO2 concentration to ±1.5% CO2 over a range of green intensity values from 90 to 170. A practical example is presented to show how vapochromic crystals could be applied to the mixing of fluid streams in gas turbine film cooling.